PHARMACOGNOSTICAL AND PRELIMINARY PHYTOCHEMICAL SCREENING OF AAVAARAI VIDHAI CHOORANAM - Ks, Uma; P, Parthiban; S, Kalpana (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: To study the organoleptic characters, physio chemical properties and preliminary phytochemicals screening of Siddha formulations Aavaarai Vidhai Chooranam (AVC). Methods: The study drug, AVC was prepared as per procedure given in the text Neerizhivu maruthuvam. Organoleptic characteristics were assessed by appearance, colour, taste and odour. The physiochemical property of trial drug was screened for moisture content, total ash value, acid insoluble ash, water soluble extractive value, alcohol soluble extractive value, pH, reducing sugar, total sugar, total solid content and fat content. Preliminary Phytochemical evaluation of AVC was carried out by the standard procedure. The drug was screened for alkaloids, amino acids & proteins, anthraxquinone, carbohydrate, flavonoids, glycosides, phenols quinones, resins, saponins, steroids tanins, terpenoids and sugar. For which the aqueous extraction of the trial drug was taken by dissolving the 5 g of sample with 50 ml of distilled water and heated over water bath at 60Â°C. Then extract was filtered and used the filtrates for testing. Results: The trial drug, AVC shown organoleptic characters as per literature evidence, physiochemical properties as moisture content, total ash value, acid insoluble ash, water soluble extractive value, alcohol soluble extractive value, pH, reducing sugar, total sugar, total solid content and fat content were found within normal limits, preliminary phytochemical test showed the presence of flavonoids, tannins, steroids, terpenoids, alkaloids, carbohydrate, proteins, phenols and sugar. Conclusion: Organoleptic characters, physio chemical properties and preliminary photochemica shows that the drug has the quality and potency to treat against diabetes mellitus. To confirm this activity, further research should be done to assess the safety and efficacy of the drug AVC.